Contemporary military strategy and the Global War on Terror : US and UK Armed Forces in Afghanistan and Iraq 2001-2012 - Finlan, Alastair (New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2014)
This title offers an in-depth analysis of US/UK military strategy in Afghanistan and Iraq from 2001 to the present day. It explores the development of contemporary military strategy in the West in the modern age before interrogating its application in the Global War on Terror. The book provides detailed insights into the formulation of military plans by political and military elites in the United States and United Kingdom for Operation Enduring Freedom and Operation Iraqi Freedom.
Contemporary military strategy -- The Afghan conundrum -- Operation Enduring Freedom -- US/UK "strategy" in Afghanistan: the first five years (2001-2006) -- The Iraq puzzle -- Operation Iraqi Freedom -- US/UK "strategy" in Iraq: the first five years (2003-2008) -- Contemporary military strategy and the Global War on Terror.
Includes bibliographical references (pages 201-207) and index.
Keywords: Afghan War, 2001-2021.; Iraq War, 2003-2011.; Strategic culture -- United States; Military relations